Microeconomics: Theory & Applications with Calculus - Perloff (Addison Wesley, 2012)
To explain how individuals and firms allocate resources and how market prices are determined, economists use a model: a description of the relationship between two or more economic variables. Economists also use models to predict how a change in one variable will affect another variable.